Chemical Composition and Biological Activities of the Essential Oils of Leptospermum petersonii and Eucalyptus gunnii - Caputo, Lucia; Smeriglio, Antonella; Trombetta, Domenico; Cornara, Laura; Trevena, Greg; Valussi, Marco; Fratianni, Florinda; De Feo, Vincenzo; Nazzaro, Filomena (Frontiers in Microbiology, 2020)
Many essential oils (EOs) produced by plants belonging to Myrtaceae family show antimicrobial and biocidal activity. The aims of this study were to characterize the chemical composition and to evaluate the antimicrobial and phytotoxic potential of the EOs from Leptospermum petersonii chemotype ‘Variety B’ and Eucaliptus gunnii, native to Australia. GC-MS analyses identified 64 and 24 components in L. petersonii and E. gunnii EOs, respectively. Geranyl acetate (31.4%) and 1,8 cineole (33.0%) are the main compounds for L. petersonii and E. gunnii EOs, respectively. The analysed sample of L. petersonii belongs to the chemical variety ‘B’. The EOs were tested against some Gram-positive (Staphylococcus aureus and Listeria monocytogenes) and Gram-negative (Escherichia coli and Pseudomonas aeruginosa) pathogenic strains and against the phytopathogen, Pectobacterium carotovorum. The antimicrobial activity of E. gunnii EO was, in some cases, much more vigorous than that exhibited by L. petersonii. E. coli and P. aeruginosa were used as tester strains to evaluate the potential activity of the two EOs in inhibiting or attenuating the microbial virulence, evaluated through the swarming motility test and through their capability to form biofilm onto one or more supports. The two EOs exhibited different strength. Moreover, the possible in vitro phytotoxicity of the EOs against germination and initial radical elongation in seeds of radish, lettuce, garden cress, tomato, Italian ryegrass and purslane, was studied. L. petersonii EO resulted inhibitory for radical elongation of S. lycopersicum and germination of R. sativus, whereas E. gunnii EO showed no phytotoxic activity.